Capturing the Voices through Lenses: A Photovoice-Based Needs Assessment of Ronggot Elementary School - Cincy Merly Gecolea (Research Synergy Foundation, 2026)
This study aimed to conduct a comprehensive needs assessment at Ronggot Elementary School, located in the remote Sitio Ronggot in Calamba City. Due to its geographical isolation and vulnerability to natural disasters, the school faces significant challenges that affect both pupils and teachers. The participants of the study were the 20 pupils and 5 teachers of Ronggot Elementary School. Photovoice was utilized as the main research design and focus group discussion was employed to gather data. Results of the comprehensive analysis of the current needs of Ronggot Elementary School, including its two locations, Bukid Learning Hub and Lecheria Integrated School, highlight the need for improved classrooms, technology access, transportation services, and sanitation facilities for pupils, as well as conducive workspaces and internet connectivity for teachers. Additionally, the assessment underscores the need for school relocation to improve accessibility and community engagement. The study concludes that addressing these issues through an evidence-based projects will significantly improve the educational experience and overall well-being of the school community. As a result, the researcher developed a school-community partnership projects, entitled Project AKAP (Alay mo, para sa Kinabukasan at Pangarap ng Batang Sitio and Isang Daan, Daan sa Kinabukasan. It is recommended that the crafted projects be disseminated to proper authorities for appropriate action